2009
DOI: 10.1016/j.ijid.2009.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Underreporting and underestimation of gonorrhea cases in the Taiwan National Gonorrhea Notifiable Disease System in the Tainan region: evaluation by a pilot physician-based sentinel surveillance on Neisseria gonorrhoeae infection

Abstract: The underreporting of gonorrhea identified in this pilot is substantial. An overhaul of Taiwan's NGNDS that streamlines the reporting procedures and the requirement for laboratory confirmation, along with a continuing medical education program is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The pathogens with highly contagious and/or public risk should be totally monitored with mandatory reporting [81]. However, the surveillance systems also have the limitation of underreporting or a lapse of surveillance [82]. The exact incidence and prevalence of PCP are difficult to determine, because the large surveillance system for PCP is not available worldwide, regardless of the clinical burden and severity.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogens with highly contagious and/or public risk should be totally monitored with mandatory reporting [81]. However, the surveillance systems also have the limitation of underreporting or a lapse of surveillance [82]. The exact incidence and prevalence of PCP are difficult to determine, because the large surveillance system for PCP is not available worldwide, regardless of the clinical burden and severity.…”
Section: Discussionmentioning
confidence: 99%
“…Under-diagnosis may arise when biological samples are not requested from or provided by patients, where there are budget restrictions forcing healthcare professionals to limit their requests for testing samples, lack of knowledge of which tests to perform, inadequate diagnostic tools, or due to restrictions of laboratory testing regimes (regulations on which tests to apply routinely, and lack of availability of more specialised tests). Under-notification may result from an inadequate reporting system or lack of knowledge of when, for which diseases and how to report correctly including knowledge of ICD codes [25-29]. The proportion of cases reported is often higher where there is a legal requirement to report (some diseases or pathogens have mandatory reporting statuses) [30] or where there are incentives for healthcare workers to request or test biological samples from patients or to report results [26].…”
Section: Introductionmentioning
confidence: 99%
“…In Taiwan, the overall prevalence based on National Gonorrhea Notifiable Disease System was 55 per 100,000 people, 36,37 although the number was likely to be underestimated. 38 The prevalence of genital chlamydial infection was not available because it is not a notifiable disease and has not been studied in the general population. Studies on high school students in the USA, however, showed that the prevalence of gonococcal infection tended to be lower than that of chlamydial infection.…”
Section: Discussionmentioning
confidence: 99%